2018
DOI: 10.1016/j.esxm.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Malleable Penile Implant Is an Effective Therapeutic Option in Men With Peyronie’s Disease and Erectile Dysfunction

Abstract: BackgroundThe inflatable penile prosthesis (IPP) is typically the preferred implant for Peyronie’s disease (PD) and malleable penile prostheses (MPPs) have been discouraged.AimsTo evaluate the effectiveness and patient satisfaction of the MPP vs IPP in patients with PD.MethodsMen with PD and erectile dysfunction who elected for penile implant surgery constituted the study population. Preoperatively, demographic and comorbidity parameters were recorded. Curvature was measured with a goniometer at maximum rigidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Habous M et al observed nearly similar satisfaction rates of 4.4 ± 0.7 and 4.3 ± 0.8 (on a 5-point Likert scale) with SPP and IPP in PD respectively. 17 Similarly, the 3 patients with PD in our series who received Shah PP reported the maximum overall satisfaction of 4 on a scale 0–4.…”
Section: Discussionmentioning
confidence: 58%
“…Habous M et al observed nearly similar satisfaction rates of 4.4 ± 0.7 and 4.3 ± 0.8 (on a 5-point Likert scale) with SPP and IPP in PD respectively. 17 Similarly, the 3 patients with PD in our series who received Shah PP reported the maximum overall satisfaction of 4 on a scale 0–4.…”
Section: Discussionmentioning
confidence: 58%
“…The IPP is favored for men with PD because of concerns regarding persistent deformity, lack of girth enhancement, limited concealment and even partner dissatisfaction, but recent work has found reported high patient satisfaction rates with malleable prostheses as well 129–131 . This has important implications, as malleable devices are more accessible and less expensive in some regions of the world.…”
Section: Surgerymentioning
confidence: 99%
“…Peyronie's disease MPP have been successfully used in men with a history of Peyronie's disease (PD). Habous et al from Saudi Arabia evaluated patient satisfaction and effectiveness of the MPP vs. IPP in patients with PD [25]. In this study, 166 men with ED and PD were evaluated for 24 months after the insertion of a MPP or IPP.…”
Section: The Use Of a Mpp In Select Population Of Patientsmentioning
confidence: 99%